Realidad Tras “El Telón de la Inclusión Laboral” en la Ciudad de Guayaquil-Ecuador - Gallegos Erazo, Franklin (2019)
The present study sought to describe the characteristics of the profiles of people with disabilities who are not employed in the city of Guayaquil-Ecuador. The sample was of 366 profiles obtained from the labor integration service for people with disabilities belonging to the national federation of Ecuadorians of physical disability, under a quantitative approach and non-experimental design, a descriptive analysis of the data was made, showing the results through of frequency graphics. Among the findings found that the profiles of this human group have greater weaknesses than strengths, which prevent their employment, among them are: a) low level of education, b) inadequate or little work experience.